2004
DOI: 10.1163/1568560043696245
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the anti-inflammatory and analgesic properties of the extract of Russelia equisetiformis (Schlecht & Cham) Scrophulariacae

Abstract: A methanolic extract of Russelia equisetiformis whole plant was studied for anti-inflammatory and analgesic activities in rats and mice using carrageenan-induced rat paw oedema, acetic-acid-induced writhing and tail-flick test. The extract, at 10, 20 and 40 mg/kg, significantly (P <0.05) inhibited carrageenan-induced oedema in rats. Abdominal constriction induced by acetic acid was also inhibited by the extract, within the same dose range. The extract at the same dose also prolonged the latency period in the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…The plants were selected based on the availability of plant materials and because of the many significant studies on their medicinal uses, such as anti-inflammatory, anti-diabetic, anti-hypertensive, anti-cancer and anti-viral properties [6,7,8,9,10,]; and removal of pollutants from wetlands [11,12] These plants have rich histories of medicinal value. Research demonstrates the anti-diabetic activity of CA [6,23,29] and anti-inflammatory activity of RE [8]. CO has a history of use for its' anti-inflammatory and anti-cancer properties [13].…”
Section: Introductionmentioning
confidence: 99%
“…The plants were selected based on the availability of plant materials and because of the many significant studies on their medicinal uses, such as anti-inflammatory, anti-diabetic, anti-hypertensive, anti-cancer and anti-viral properties [6,7,8,9,10,]; and removal of pollutants from wetlands [11,12] These plants have rich histories of medicinal value. Research demonstrates the anti-diabetic activity of CA [6,23,29] and anti-inflammatory activity of RE [8]. CO has a history of use for its' anti-inflammatory and anti-cancer properties [13].…”
Section: Introductionmentioning
confidence: 99%
“…Medicinally, the plant is used for the treatment of diabetes and leukemia in Southwestern, Nigeria[ 10 ]. The extract of the plant has been reported to possess antibacterial, analgesic and antiinflammatory activities[ 11 ]. Recently, two flavonoid compounds isolated from R. equisetiformis were reported to have potential analgesic activity[ 12 ].…”
mentioning
confidence: 99%
“…In Colombia, the fresh entire plant decoction is taken orally to cure kidney stones 7 , while the whole plant and its aerial infusion is utilized as a complementary therapy for DM2 patients in Mexico [8][9] . An anti-oxidant, anti-inflammatory 6 , antinociceptive and analgesic properties [10][11] were observed for different extracts of R. equisetiformis, together with antibacterial 12 , antimicrobial, cytotoxic 13 , CNS depressant 14 , hepatic functions activity 5 , hair growth promoter 15 and membrane stabilizing activities 16 . The present study reported the separation and structure elucidation of eight compounds (Fig 1) from different fractions of the aerial parts of R. equisetiformis, in addition to evaluate the LD50, antiinflammatory, antipyretic and antihyperglycemic activities of it.…”
Section: Introductionmentioning
confidence: 99%